2007
DOI: 10.1111/j.1442-200x.2007.02333.x
|View full text |Cite
|
Sign up to set email alerts
|

Birthweight and risk factors for cardiovascular diseases in Japanese schoolchildren

Abstract: BW is related to serum concentrations of adiponectin and uric acid. However, weight velocity was a stronger determinant of serum adiponectin and uric acid levels than BW in Japanese schoolchildren. Thus, it may be important to control weight gain to prevent the development of ACHD in children, especially in children with LBW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
16
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
(67 reference statements)
10
16
1
2
Order By: Relevance
“…The association of BMI gain with abnormal glucose homeostasis and markers of early atherosclerosis in children (15,27) is similar to the trend we observed between BMI gain and risk for SDB after adenotonsillectomy. The similarity in these trends raises the important question of whether SDB is one link between a high rate of BMI gain during childhood and abnormal glucose homeostasis and cardiovascular disease in adulthood.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The association of BMI gain with abnormal glucose homeostasis and markers of early atherosclerosis in children (15,27) is similar to the trend we observed between BMI gain and risk for SDB after adenotonsillectomy. The similarity in these trends raises the important question of whether SDB is one link between a high rate of BMI gain during childhood and abnormal glucose homeostasis and cardiovascular disease in adulthood.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have demonstrated that the inflammatory consequences of obesity and its cardiovascular morbidity are influenced by the rate of weight gain over time independent of actual weight (15)(16)(17)(18)(19). Thus, the degree of adiposity and rate of weight gain may reflect different disease processes (20,21).…”
mentioning
confidence: 99%
“…Based on the findings of Malik et al, the rate of LBW infants was higher in the women over 35 than those over 18 years of age (16). A significant association was also observed between the mothers' occupation and education, and low birth weight, which has been confirmed by other studies (17)(18)(19). In the present study, it has been well demonstrated that if Birth spacing increases, the likelihood of declined low birth weight will increase, and this is a result confirmed by Klufio et al (18).…”
Section: Discussionsupporting
confidence: 91%
“…Entretanto, a velocidade de ganho de peso foi mais determinante para os níveis séricos destes elementos, do que apenas o BPN. Esses dados reforçam a importância do controle de peso para prevenir o desenvolvimento de aterosclerose coronariana em crianças, especialmente aquelas com histórico de BPN (KANESHI et al, 2007).…”
Section: Bpn E Obesidadeunclassified
“…No fígado, ela inibe tanto a expressão das enzimas que estimulam a neoglicogênese quanto à produção de glicose (KANESHI et al, 2007).…”
Section: Bpn E Obesidadeunclassified